Revisiting the fatawa in disposing Islamic literature materials in Malaysia - Zainan Nazri, Nurul Jannah; Fatah Yasin, Raudlotul Firdaus; Samsudin, Sofiah; Ghazali, Natirah Azira (2018)
The advancement of the technology in printing media has led to the increasing number of paper-based published Islamic literature materials. Eventually, the demand to provide a means of disposing unused published materials has also increased. In Malaysia alone, according to the latest statement of JAKIM, JAIS and JAWI, they are not able to accept any unused published Islamic literature materials for disposal for the time being due to the large volume at the collection center